Hubungan perceived susceptibility dan perceived benefits dengan pemberian ASI eksklusif pada balita di Puskesmas Kasihan I Bantul - Fatimah Dewi Anggraeni; Eva Putriningrum (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Exclusive breastfeeding is breast milk given to babies from birth for six months without adding and / or replacing it with other foods or drinks. Based on Article 6 in the same government regulation, every mother who gives birth must provide exclusive breastfeeding to the baby born to her. Based on the results of Riskesdas 2018, the proportion of breastfeeding patterns for infants aged 0-5 months in Indonesia was 37.3% exclusive breastfeeding, 9.3% partial breastfeeding, and 3.3% predominant breastfeeding.Objective: to determine the relationship between the variable perceived susceptibility and perceived benefits with exclusive breastfeeding for children under five in the working area of Kasihan I Health Center,Methods: This study is an analytic survey study using a cross sectional approach. The population are mothers who had babies aged 6-24 months. The statistical test used bivariate chi square statistical testResults: mothers who do not provide exclusive breastfeeding are 26.3% (10 people). In the variable perceived susceptibility, most of it was in the high category of 60.53% (23 people), the variable of perceived benefits, mostly in the high category was 60.53% (23 people). There is no relationship between perceived susceptibility and breastfeeding (p = 0.122; OR = 3.167). There is a relationship between perceived benefits and giving (p = 0.021; OR 5.833)Conclusion: There is a relationship between perceived benefits and exclusive breastfeeding, while the variable perceived susceptibility has no relationship with exclusive breastfeeding.